Dialektika Realitas Kemanusiaan Dan Hukum Al-Qur'an - Muhammad Erfan (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
From the fourth traditional Islamic studies that have established, namely fiqh studies (ilm al-fiqh), kalam studies (ilm alkalam), tasawwuf studies (ilm al-tasawwuf), and Islamic philosophy (al-falsafah or al-hikmah), Islamic lawknown fiqhis a dominant discipline in the Moslem comprehension about their religion. In this domain, Islamic law is a piety parameter for Moslem in embodiment the value of such Quranic law. But, there is a fact that the values of Quranic law have a historical dimension of Arabic community. Therefore, there must an effort to uncover the role of Arabic tradition toward Quranic law productivity. Although in the other domain, al-Quran is a transcendental word of Allah, but when al-Quran have manifested in Arabic life, and Arabic language is an official language of it, its meant al-Quran is a part of Arabic reality. Besides that, Quranic text has also growth in line with Arabic reality. Hence, Quranic law which derived through text is a divine respond, universally or partially, toward a reality in which there is a historical humanity of Arabic community. Consequently, at the time is in outside of Arabic reality, Quranic laws must be criticized and adjusted with such contemporary reality.